Kandungan Amilum Mikrospora Dendrobium Anita Selama Perkembangan Bunga dan Induksi Androgenesis = Starch Content of Dendrobium anita Microspore During Flower Development and Androgenesis Induction - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The aims of this research are to know stadium where starch is start formed during microspore development, to know correlation microspore starch content to anther growth, and microspore viability during androgenesis induction. The resulth show that starch is start formed in group I (0,8-1, 2 cm) microspore (29 ppm/anther). Microspore atrch content has positive correlation (P < 0,01) to anther growth until group IV (2,32,7 cm) and positive correlation (P < 0,01) to microspore viability during androgenesis induction.